Lessons learned from the implementation of reduced-impact logging in hilly terrain in Sabah, Malaysia - Pinard, M.A.; Putz, F.E.; Tay, J. (2000)
Between 1992 and 1997, about 2400 ha of old growth dipterocarp forest in southeastern Sabah was logged to reduced-impact logging (RIL) guidelines as part of a pilot carbon offset project. Harvesting planning, vine cutting, directional felling and skidding restrictions contributed to a reduction in stand damage from 50% to 28% of the original stems; damage to soil was reduced from 13% to 9% of total area in RIL relative to conventional logging areas. Residual stands in RIL areas had greater vertical structure and better stocking of commercial timber species than stands in conventionally logged areas, with positive gains for conservation of biodiversity and sustainability of timber production. Steep terrain and the lack of predictable dry periods were constraints on the ground-based skidding system, and resulted in large volumes of timber being inaccessible, and in production delays caused by wet weather. Introduction of an aerial yarding system in this region would allow a greater proportion of the areas to be harvested in an environmentally acceptable way.